Innovation Policy Implementation in Indonesia: Perspective of Triple Helix - Anugerah Yuka Asmara; Retno Kusumastuti (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2021)
Innovation is present to accelerate economy growth in both advanced and developing countries. It brings about many changes in several fields including changes in public policy. In developing countries, public policy for innovation is not easily implemented, including in Indonesia. Though Government of Indonesia has many inovation programs at national level, but practice of innovation policy is still not optimal. This study is s qualitative research method using primary and secondary data sources. In nut shell, This study is aimed to explain key determinant factors hindering innovation policy in Indonesia, particularly to answer why classic issue of innovation problem is still unresolved in recent condition. The study finding is that vague mechanism to coordinate among each ministry, R&D institutions/universities, and enterprises is homework of Government of Indonesia.Keywords: Innovation, Policy, Government, Indonesia